Histopathological changes in tissues of experimentally infected local chickens with biting lice Menacanthus stramineu - M.AL-Mayali, Hadi; I.AL-Lebawi, Fatima (Al-Qadisiyah Journal of Pure Science, 2018)
The study of results showed histopathological changes in each of (skin, muscle, liver, kidney, spleen and small intestine) represented by proliferation fibrous connective tissue in layer of the dermis and infiltration of inflammatory cells as well as hyperplasia in epithelial layer of the epidermis also appeared degeneration and necrosis of the muscle fibers where appeared free nuclei with infiltration of inflammatory cells out of the blood vessels in addition to the appearance bleeding within the muscle fibers in the liver there appeared congestion of central veins with loss of the geometric structure of the liver tissue and infiltration of inflammatory cells near the central vein with fatty degeneration of the liver cells as happened atrophy of the intestinal villi and crashing and alienation in the villi that lining the vertical cells. In the kidney, noted presence of severe bleeding in the renal tissue and necrosis of the cell lining of renal tubules twisted with atrophy of the renal glomeruli. In the spleen ,the results showed atrophy an exhausted pulp white with severe proliferation in red pulp and incidence of hemorrhage and necrosis widely in the lymphoid tissue of the spleen.also appeared the air sacs in lungs full of red blood cells with a large clot inside a blood vessel.